Studies on freshwater Copepoda : a volume in honour of Bernard Dussart - Defaye, Danielle; Suárez, Eduardo, 1960-; Vaupel Klein, J. C. von (Crustaceana monographs ;, 2011)
Bernard Dussart's contributions to limnology and freshwater copepodology comprise over 200 scientific papers, and his frequent travels have greatly stimulated interest in freshwater biology world-wide. This book presents a selection of recent research on the Copepoda of continental waters: a worthy tribute.